2017
DOI: 10.25110/arqsaude.v21i1.2017.5389
|View full text |Cite
|
Sign up to set email alerts
|

Infusão Contínua Versus Intermitente De Meropenem Na Prática Clínica

Abstract: Ligiane de Lourdes da Silva 5 SIMONATO, B. S.; TEIXEIRA, G. C.; REBECCA, E. S. W.; ROSS, C.; SILVA, L. de L. da. Infusão contínua versus intermitente de meropenem na prática clínica. Arq. Cienc. Saúde UNIPAR, Umuarama, v. 21, n. 1, p, 59-64, jan./abr. 2017. RESUMO:Analisar as evidências científicas relacionadas ao tempo de administração endovenosa do Meropenem na prática clínica. Trata-se de uma revisão integrativa de literatura, retrospectiva, de natureza descritiva, com abordagem quantitativa com destaque pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
2
0
4
Order By: Relevance
“…Na administração de medicamentos, infusões endovenosas podem ocorrer de forma contínua ou intermitente, rápida entre 3 e 5 minutos, em 30 minutos, ou em períodos de 1 a 3h, considerando fatores como condições do paciente e possíveis complicações (16) . A concentração da substância é importante fator a ser considerado.…”
Section: Discussionunclassified
“…Na administração de medicamentos, infusões endovenosas podem ocorrer de forma contínua ou intermitente, rápida entre 3 e 5 minutos, em 30 minutos, ou em períodos de 1 a 3h, considerando fatores como condições do paciente e possíveis complicações (16) . A concentração da substância é importante fator a ser considerado.…”
Section: Discussionunclassified
“…Therefore, it is important that a prescription contains, in addition to the dose, the infusion time so as not to influence the effectiveness of this medication 16 . Studies have shown that carbapenems, such as meropenem, in prolonged infusion for 3 hours demonstrate superiority in pK/pD and lower chances of adverse events 17 .…”
Section: Discussionmentioning
confidence: 99%
“…This antimicrobial provides coverage against several microorganisms, being useful and widely prescribed for the treatment of severe and nosocomial infections in hospitalized patients. [1][2][3] Meropenem, such as some other traditional antimicrobial agents, is a time-dependent drug and has a bactericidal action that inhibits bacterial cell wall synthesis. 3,4 For time-dependent drugs, the main parameter associated with therapeutic success is the percentage of time that the levels of antibiotics at the infection site exceed the minimum inhibitory concentration (%fT > MIC) of the pathogen.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%